SUMBANG PERILAKU PEREMPUAN MINANGKABAU DALAM KARYA SENI LUKIS REALIS KONTEMPORER - Drs. Abd. Hafiz, M.Pd., SASFERI YENDRA, Drs. Erfahmi, M.Sn., (Serupa The Journal of Art Education, 2017)
The purpose of creation of this final work is to remind the indigenous Minangkabau women how to dress well in the Minangkabau region. The method for creating this thesis uses five phases: preparation, elaboration, synthesis, the realization of the concept, and the stage of completion, as well as the latter held an exhibition of paintings using the medium of acrylic paint on canvas with a brush stroke technique, style Contemporary Realists. Produce ten paintings with titles 1.) Budaya Barat, 2.) Ketat, 3.)Sumbang Duduak, 4.) Manenun, 5.)Sumbang Pakai, 6.) Bakarajo, 7.)Adat jo Kekinian, 8.) Simbol Nagari, 9.) Niru, 10.)Kato Mandaki.